Study on factor that contributes to the employee’s performance / Nur Ashikin Saharudin and Wan Nurliyana Wan Zaizin - Saharudin, Nur Ashikin; Wan Zaizin, Wan Nurliyana (Faculty of Administrative Science and Policy Studies, 2012)
Employees basically refer to people who work for another to get salary or any return and who does not provide these services as part of an independent business. The employees are playing the important role because they are the ones who provide services and products and the organization will not function smoothly without them. Therefore, the organization must cooperate and motivate the employees to get a better result. Building a positive communication with employees is important because they are the organization’s best ambassadors or loudest critics, depending on how fast they get relevant information and the context in which it is received (Howard, 1998). As long the communication between the employers and employees doing great, the employees will feel that they are value towards the organization and it automatically will build the loyalty, commitment and satisfaction in them. Communication is important in our daily life and so does in an organization. Gamble and Gamble (1999) stated: “Communication is the core of our humanness”, and that “how we communicate with each other shapes our lives and our world”. Communication skills can help us to get know each other or to confront in any situation and it may increase our critical thinking skills, flexibility and integrity.